Handbook of research on the adverse effects of pesticide pollution in aquatic ecosystems - Wani, Khursheed Ahmad; Mamta, 1987- (IGI Global, 2018)
"This book provides readers with a better understanding of the consequences of pesticide use in different ecosystems and its implications on water bodies around the world. The potential risk to human health, extensive pollution to the environment, their accumulation potential in different trophic levels is a matter of great concern to researchers and is discussed"--